Pengaruh Akuntansi Akrual dan Pengungkapan Lingkungan terhadap Koefisien Respon Laba pada Perusahaan Terindeks JII - Karuni, Mudita Sri (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This research is aimed to identify whether accrual accounting and environmental disclosure influence Earning Response Coefficient (ERC). The data were collected by using document and library method. The dependent variable in this research is ERC that measured by the market response to the unexpected earnings. The independent variable is accrual accounting and environmental disclosure, which was tested on the firm’s total information disclosure of Corporate Social Responsibility (CSR. This research used Panel Data Regression. A total sample of 16 companies listed in Jakarta Islamic Index (JII) for five years (2014-2018) was used to perform the analysis and hypotheses testing. The result of this research is that accrual accounting has no significant relationship with the ERC, and CSR information disclosure has a positive and significant relationship with the ERC.